Influence of Celebrity Worship Motives (CWM) on Customer Brand Relationship (CBR) towards Services Brands - Perera, G.N.R.; Dissanayake, D.M.R.; Dissanayake, D.M.R.; Wanninayake, W.M.C.B.; Wanninayake, W.M.C.B. (Archives of Business Research, 2018)
Celebrity Worship Motives (CWM) determines how celebrities and consumers engage through a psychological bond. CWM intensifies the effectiveness of celebrity endorsement when it results brand evaluations. CBR has been empirically tested as one of the brand-related behaviors resulted by different brand stimulus including celebrity endorsements. Moreover, CWM and CBR found to be significant research notions within celebrity endorsements-related studies whilst services sector is denoted as a specific research gap within. Inline, this study examines how CWM relates with CBR considering Sri Lanka as a specific context to of services sector. A deductive approach was followed to hypothesize the research questions. A questionnaire was employed as the research instrument. Sample was determined followed a multistage cluster sampling method, and finally 240 respondents were considered for the final analysis. Study used quantitative methods including inferential and descriptive statistical tools to analyze the data. Study found CWM impacts on CBR whilst aspirational motives was noted as a most significant influencer towards CBR. Paper concludes practical implications to industry and future research priorities were proposed accordingly.